Brown Adipose Tissue: Multimodality Evaluation by PET, MRI, Infrared Thermography, and Whole‐Body Calorimetry (TACTICAL‐II) - Li Sun; Sanjay Kumar Verma; Navin Michael; Siew Pang Chan; Jianhua Yan; Suresh Anand Sadananthan; Stefan Gerardus Camps; Hui Jen Goh; Priya Govindharajulu; John J. Totman; David W. Townsend; Julian Pak‐Nam Goh; et al. (2019)
This study aimed to compare the associations of positron emission tomography (PET), magnetic resonance (MR), and infrared thermography (IRT) imaging modalities with energy expenditure (EE) after brown adipose tissue (BAT) activation using capsinoid ingestion and cold exposure.Twenty participants underwent PET-MR, IRT imaging, and whole-body calorimetry after capsinoid ingestion and cold exposure. Standardized uptake values (SUV) and the fat fraction (FF) of the supraclavicular brown adipose tissue regions were estimated. The anterior supraclavicular temperature (Tscv) from IRT at baseline and postintervention was measured. Two-hour post-capsinoid ingestion EE and post-cold exposure EE served as a reference to correlate fluorodeoxyglucose uptake, FF, and Tscv for BAT assessment. IRT images were geometrically transformed to overlay on PET-MR for visualization of the hottest regions.The supraclavicular hot spot identified on IRT closely corresponded to the area of maximal fluorodeoxyglucose uptake on PET images. Controlling for body weight, post-cold exposure Tscv was a significant variable associated with EE (P = 0.025). The SUV was significantly inversely correlated with FF (P = 0.012) and significantly correlated with peak of Tscv during cold exposure in BAT-positive participants (P = 0.022).Tscv correlated positively with EE and was also significantly correlated with SUV after cold exposure. Both IRT and MR FF are promising methods to study BAT activity noninvasively.